Age structure and population momentum in South Korea - Whang, Choyi; Choi, Seulki (Journal of Asian Sociology, 2015)
The purpose of this research is to explain why the Korean population is still growing despite a very low fertility level and a changing age structure in Korea. To analyze the impact of age structure on the future population growth, population pyramids and estimations of population momentum are used. Population momentum then is further decomposed into stable and nonstable momentums. Decomposition allows the impact of low fertility on future population growth to be analyzed in two steps. We conclude that the history of high fertility has accumulated positive momentum and this momentum is still in effect for continuous population growth. In addition, this research provides a reason why population policy needs to be planned in a longer timeframe.